Design and Implementation of A Web Based Ordering System - Cao, Jingwen (Journal of Theory and Practice of Management Science, 2025)
Working staff spend much more time using computers than using mobile phones, making it more convenient to order meals on computers compared to using mobile apps. Therefore, a web-based ordering system has been designed. The system adopts a front-end and back-end separation mode. The front-end adopts Vue.js framework, the server uses Node.js, and the database uses MongoDB. This system can effectively meet the ordering needs of users on web pages. The ordering system has been validated and tested to meet user needs and has practical value.